Reviewing Some Implications of the Green Economy for Higher and Further Education Institutions - Godwell Nhamo (Environmental Association of Southern Africa, 2014)
The world is set to apply green economy as a framework for achieving sustainable development, eradicate poverty and inequality and create jobs. This reality follows the consensus on green economy by global leaders during Rio+20 in June 2012. At the centre of the green economy is the need to address negative impacts associated with one of the global challenges of our epoch, climate change. Higher education (including further education) is viewed by many as an enabling platform for the generation and acquisition of green economy knowledge and skills for the future we want. The question this paper seeks to address is: are African institutions of higher education green economy ready? This question is not only limited to the curricula, but to broader impact areas in higher education that include the institutionalisation of green economy in policy, research and research management structures, in depth understanding of the green economy concept and the manner in which it links to existing paradigms like sustainable development as well as higher education- private sector partnerships. The paper shows that there are a number of emerging initiatives that can be seen to be developing green economy education and training in higher/further education contexts, but that much more needs to be done. The paper shows a 'slow awakening' to the green economy call as revealed by activities from the United Nations Educational, Scientific and Cultural Organisation (UNESCO), the Environmental Education Association of Southern Africa (EEASA) and selected universities and private sector initiatives.